Scientific Thinking About Legal Truth - Rosenzweig, Gal (Frontiers in Psychology, 2022)
In the criminal process, the fact finders assess the validity of impressions reported by witnesses based on their perceptions and determine what has happened in reality. However, these impressions are not subject to any external validity check. The Innocence Project revealed the failure of this subjective method and showed how it can lead to innocent convictions. The legal literature has examined ways to manage the risk of mistakes, but these ways are inconsistent with the scientific understanding of the need for external validity measurements, suggesting the need for new ways of thinking about the legal search for truth and justice.